Experimental and computational investigation of thermal performance and fluid flow in two-phase closed thermosyphon - Cho, Sehyeon; Kong, Daeyoung; Geum, Gyohoon; Kang, Sukkyung; Hyeuk Seo, Jin; Kim, Jun Soo; Lee, Seong Hyuk; Lee, Jungho; Lee, Hyoungsoon (Applied Thermal Engineering, 2023)
Over the last two decades, energy recovery has become increasingly important in the transition from fossil fuels to green energy. Waste heat recovery, such as the two-phase closed thermosyphon (TPCT) type of heat exchanger, is a highly efficient energy recovery technique. However, accurately predicting the thermal performance and flow patterns in TPCTs is challenging due to the complex physics of phase-change phenomena. A new predictive model is suggested that can provide improved accuracy when predicting thermal performance and flow patterns in TPCTs. An experimental study was conducted to acquire the data, and the results were compared with computational results obtained from the new proposed model. The model uses the volume of fluid (VOF) model with the Lee model for the phase change process in OpenFOAM v2106. To increase accuracy, the saturation temperature and vapor density were defined as a function based on the mass balance in the TPCT. In addition, a simulation was conducted to predict the thermal performance and flow patterns in a TPCT, during which the effects of the empirical value of the mass transfer intensity factor were investigated. The study is expected to provide insights into phase-change modeling with high accuracy and an understanding of the thermal characteristics of TPCTs.
Keywords: Computational investigation; Energy recovery; Experimental investigations; Fluid-flow; OpenFOAM; Thermal flows; Thermal fluids; Thermal Performance; Two-phase closed thermosyphon; Waste-heat recovery; Boiling; Condensation; OpenFOAM; Two-phase closed thermosyphon; Waste heat recovery